PENGARUH IKLIM KERJA DAN KETERAMPILAN TERHADAP KINERJA KARYAWAN DEPARTEMEN PRODUKSI PT. BUKIT SEMBILAN KABUPATEN KAMPAR - Hadi, Zupri; Hendriani, Susi; Daulay, Iwan Nauli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted on the production department employees at PT. Bukit Sembilan Kampar Regency with the aim to analyze the influence of work atmosphere variables and skills of employees of the production department at PT. Bukit Sembilan Kampar Regency. Sampling was done by the slovin method 73 samples were selected as respondents by using stratified random sampling in the division. The analytical method used is descriptive quantitative methods, data analysis carried out partially and simultaneously (multiple linear regression analysis with SPSS version 21.0). The results of simultaneous testing (F test), indicating that all independent variables studied have a significant effect on employee performance variables. Partial regression test (t test) showed that more skill variables significantly influence the performance of the production department employees at PT. Bukit Sembilan Kampar Regency. The magnitude of the effect caused by these two variables together against the dependent variable of 29.8 %, this means that the work atmosphere and skill of variables jointly affect employee performance variables with a percentage of 29.8 %. While 70.2 %, influenced by other factors that do not participate in this study.Keywords: Work atmosphere, Skills and Employee performance